2012
DOI: 10.1007/s00264-011-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral focal surgery for the treatment of non-contiguous multifocal spinal tuberculosis

Abstract: Intervertebral focal surgery by complete debridement, deformity correction, graft fusion, and internal fixation for patients with non-contiguous multifocal spinal tuberculosis was feasible and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…[ 4 , 15 , 16 ] Polley and (2009) [ 1 ] reported that there was a higher incidence of neurology in the noncontiguous group (75%) compared to the rest of our group (58.5%). Shi et al [ 12 ] adopted complete debridement, deformity correction, graft fusion, and internal fixation for patients with noncontiguous multifocal spinal TB. A total of 29 cases achieved satisfactory deformity correction and the correction angle loss, having a significant recovery from kyphosis and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 15 , 16 ] Polley and (2009) [ 1 ] reported that there was a higher incidence of neurology in the noncontiguous group (75%) compared to the rest of our group (58.5%). Shi et al [ 12 ] adopted complete debridement, deformity correction, graft fusion, and internal fixation for patients with noncontiguous multifocal spinal TB. A total of 29 cases achieved satisfactory deformity correction and the correction angle loss, having a significant recovery from kyphosis and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, surgery is an efficient treatment for patients with spinal TB that manifests as kyphotic deformity, neurological deficit, or a huge abscess and postoperative nutritional support is also important. [ 1 , 4 , 11 , 12 ] Polley and Dunn [ 1 ] stated that those patients with skip lesions are more prone to develop neurological complications than the rest cases indicating a high incidence of surgical intervention. Identification of noncontiguous vertebral TB, symptomatic or not, however, is important because it can influence the decision of surgical intervention, the number of levels instrumented and may dictate the need for bracing of levels not surgically treated.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior-only approach is associated with relatively better clinical outcome in both adult and elderly population, but its feasibility is subjective to the accessibility of the distant focus, the degree of bone destruction, and the associated risk of injuring the iliac vessels, aorta, abdominals contents, and the spinal cord [6][7][8] . In cases with atypical presenting features where TB involved the posterior column or presented as non-contiguous lesions, multifocal, surgical approaches need to involve complete debridement with combinedanterior-posterior approaches 9,10 . Apart from the conventional surgical procedures mentioned above, some authors have also proposed new surgical techniques to treat conditions with certain characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Ultralong segmental spinal TB may result from the onset of disease because of the doctors' incomplete understanding or delayed surgical treatment during the patient's first visit [3][4][5]. The wide scope of the lesions and the number of vertebrae involved make it difficult to cure these patients.…”
Section: Introductionmentioning
confidence: 97%